Genetic evidence and historical theories of the Asian and African origins of the present Malagasy population. (22nd January 2021) - Heiske, Margit; Alva, Omar; Pereda-Loth, Veronica; Van Schalkwyk, Matthew; Radimilahy, Chantal; Letellier, Thierry; Rakotarisoa, Jean-Aimé; Pierron, Denis
Abstract: The origin of the Malagasy population has been a subject of speculation since the 16th century. Contributions of African, Asian, Indian, Melanesian, Arabic and Persian populations have been suggested based on physical and cultural anthropology, oral tradition, linguistics and later also by archaeology. In the mid-20th century, increased knowledge of heredity rules and technical progress enabled the identification of African and Asian populations as main contributors. Recent access to the genomic landscape of Madagascar demonstrated pronounced regional variability in the relative contributions of these two ancestries, yet with significant presence of both African and Asian components throughout Madagascar. This article reviews the extent to which genetic results have settled historical questions concerning the origin of the Malagasy population. After an overview of the early literature, the genetic results of the 20th and 21th centuries are discussed and then complemented by the latest results in genome-wide analyses. While there is still much uncertainty regarding when, how and the circumstances under which the ancestors of the modern Malagasy population arrived on the island, we propose a scenario based on historical texts and genomic results.